Mechanisms of Hybrid Governance: Administrative Committees in Non-Equity Alliances - Reuer, Jeffrey J.; Devarakonda, Shivaram V. (Academy of Management Journal, 2016)
Recent research on the governance of hybrid organizational forms has investigated the contractual foundations of collaborations by examining how firms craft complex contracts, as well as plan for changing circumstances during contract execution. We build upon and extend this research by considering the contractual delegation of authority to a dedicated structural interface for a collaboration. In particular, our theory suggests that partners are more likely to employ steering committees to help partners guide their interactions, address unanticipated contingencies that materialize, and mitigate incipient conflicts when partners have substantial needs for coordinated adaptation. An analysis of alliances in the biopharmaceuticals industry explicates the formal governance mechanisms that support high-tech partnerships and identifies determinants of the administrative structures firms utilize in contractual agreements to enhance their adaptive limits.